2020
DOI: 10.3389/fnins.2020.567849
|View full text |Cite
|
Sign up to set email alerts
|

Carbachol and Nicotine in Prefrontal Cortex Have Differential Effects on Sleep-Wake States

Abstract: The role of the brainstem cholinergic system in the regulation of sleep-wake states has been studied extensively but relatively little is known about the role of cholinergic mechanisms in prefrontal cortex in the regulation of sleep-wake states. In a recent study, we showed that prefrontal cholinergic stimulation in anesthetized rat can reverse the traits associated with anesthesia and restore a wake-like state, thereby providing evidence for a causal role for prefrontal cholinergic mechanisms in modulating le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 57 publications
0
6
0
Order By: Relevance
“…In contrast, cholinergic stimulation of parietal cortex in sevoflurane-anesthetized rats failed to produce behavioral arousal (Pal et al, 2018). We also demonstrated that infusion of carbachol into prefrontal cortex during slow-wave sleep reduced the latency to the onset of wakefulness and increased the time spent in wakefulness (Parkar et al, 2020). These studies suggest a causal role for prefrontal cortex in behavioral arousal.…”
Section: Introductionmentioning
confidence: 58%
See 2 more Smart Citations
“…In contrast, cholinergic stimulation of parietal cortex in sevoflurane-anesthetized rats failed to produce behavioral arousal (Pal et al, 2018). We also demonstrated that infusion of carbachol into prefrontal cortex during slow-wave sleep reduced the latency to the onset of wakefulness and increased the time spent in wakefulness (Parkar et al, 2020). These studies suggest a causal role for prefrontal cortex in behavioral arousal.…”
Section: Introductionmentioning
confidence: 58%
“…in wake state (Parkar et al, 2020). A rat study focused on thalamocortical synchronization during anesthesia demonstrated similar neural dynamics between rat and human prefrontal cortex and posited a role for prefrontal cortex in emergence from anesthesia (Flores et al, 2017).…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Given the importance of sleep to the body, sleep mechanisms have been intensively investigated. Sleep has been shown to involve many regions and nuclei in the brain, including subcortical nuclei such as the hypothalamus, brainstem, and basal forebrain, as well as the prefrontal cortex, motor cortex, anterior cingulate cortex (ACC), and primary visual cortex [ 13 , 14 , 15 , 16 , 17 , 18 ]. However, these findings have raised new questions, such as why so many nuclei as well as the cerebral cortex are involved in the maintenance of sleep or wakefulness while the detailed mechanisms underlying sleep and wakefulness are incompletely understood.…”
Section: Introductionmentioning
confidence: 99%
“… 1 Similarly, cholinergic stimulation of PFC during slow-wave sleep decreases the latency to wakefulness and increases the time spent in wakefulness. 2 Conversely, tetrodotoxin (TTX)-mediated inactivation of PFC, but not parietal cortex, delays emergence from sevoflurane anesthesia. 3 Notably, reversal of general anesthesia after carbachol delivery into PFC was associated with an increase in local acetylcholine levels, 1 which is consistent with a wide array of studies demonstrating high cortical acetylcholine levels in association with cortical activation and wakefulness.…”
mentioning
confidence: 99%